The power of positive thinking - Peale, Norman Vincent 1898-1993 (Pocket Books, 2013)
An international bestseller with over five million copies in print, The Power of Positive Thinking has helped men and women around the world to achieve fulfillment in their lives through Dr. Norman Vincent Peale's powerful message of faith and inspiration. In this phenomenal bestseller, "written with the sole objective of helping the reader achieve a happy, satisfying, and worthwhile life," Dr. Peale demonstrates the power of faith in action. With the practical techniques outlined in this book, you can energize your life--and give yourself the initiative needed to carry out your ambitions and hopes. You'll learn how to: - Believe in yourself and in everything you do - Build new power and determination - Develop the power to reach your goals - Break the worry habit and achieve a relaxed life - Improve your personal and professional relationships - Assume control over your circumstances - Be kind to yourself